Pengembangan Lembar Kerja PeSerta Didik (LKPD) Berbasis Pembelajaran Berdiferensiasi pada Materi Statistika Kelas VII SMP Negeri 1 Seluas - Noperita, Noperita; Ardiawan, Yadi; Irvandi, Wandra (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the level of validity, level of practicality and level of effectiveness of Student Worksheets (LKPD) based on differentiated learning on statistics material. The research method used in this study is the research and development method. The subjects in this study are divided into two subjects, namely development and product trial subjects. Data collection tools used in this study are validation sheets, questionnaires and tests. Based on the results of the research that has been done, it can be concluded that the Student Worksheet (LKPD) based on differentiated learning is very valid, very practical and effective to be used as a learning medium.